Evaluer à distance en temps de pandémie : le cas d'un programme de maitrise professionnelle en environnement - Champoux, Mélanie; Hillman, Ariane (2022)
At the University Center for Training in Environment and Sustainable Development (CUFE), as in many other faculties and departments, the remote changeover imposed in the context of the COVID-19 pandemic, has helped to relaunch various pedagogical reflections, in particular those related to assessment practices. The following article presents a synthesis of an empirical research carried out at the CUFE during the year 2021. The purpose of this research was to identify the evolution of the conceptions of teachers in a pandemic context with regard to the methods of evaluation alternatives to the classroom exam.